Analysis of Factors Influencing Low Back Pain (LBP) Complaints in Convection Tailors Pademangan North - Winata, Susanty Dewi; Fuk, Liem Jen; Sutanti, Yosephin Sri; Lau, Denice (Universitas Kristen Krida Wacana, 2025)
Low back pain is a disorder of the musculoskeletal system caused by ergonomic exposure, including improper work posture, sitting too long, and excessive activity. Purpose: This study aims to examine the relationship between work posture, age, length of service, gender, body mass index, last level of education, and smoking habits with LBP complaints in garment sewing workers in the Pademangan area, North Jakarta, in 2024. The research design used in this study was cross-sectional and took place in November 2024. Individual characteristics, job information, and LBP complaints were obtained from the Nordic Questionnaire about lower back problems, while the respondents' work postures were obtained using RULA (Rapid Upper Extremity Assessment). Data were analyzed using the Chi-Square test method. A total of 44 respondents (58.7%) showed unergonomic work postures based on the RULA score, and 37 respondents (49.3%) reported LBP complaints. The results of the analysis found a significant relationship between length of service and LBP complaints. Respondents with more than 5 years of work experience tend to experience LBP complaints more often than respondents with less than 5 years of work experience. Ergonomic work posture control is essential to prevent and reduce LBP complaints.